STRUCTURAL ADVANTAGE OF THE UKRAINE INDUSTRY: COMPARISON AT THE MACRO AND MESO LEVELS (Economic journal of Lesya Ukrainka Volyn National University, 2018)
From the point of view of the growing global processes of globalization and competition in commodity markets, the industrial sector of the national economy needs in-depth assessments. Its results will create the analytical basis for forming the direction of state industrial policy, in particular, at the regional level of Ukraine economy. The purpose of the article is to determine the structural advantages of industry in Ukraine and its regions on the basis of comparative assessment with the European Union (EU) member states. The author’s interpretation of the competitiveness of the industrial sector of the economy as a permanent ability to with stand competition as the result of the availability of the corresponding potential (first of all, the formed structural characteristics) is proposed, subject to the achievement of a high level of efficiency of functioning. The methodical approach and mathematical tools for assessing the competitiveness of industry are based on the determination of its internal and external efficiency. A comparative analysis of the structural advantages of industry in Ukraine and its regions and the EU-28 has been conducted on the indicators of industry’s share in economy output, gross value added of the economy, exports of airborne vehicles, as well as by the indicator of the share of airborne emissions in industrial output. By aggregating these indicators, the coefficient of structural advantages of the industrial sector of the national economy is calculated on the regional basis. As the results of calculations show, the national economy belongs to the industrial type. The Ukrainian industry is export-oriented, but low-efficiency – the 28-th place among the EU in terms of the share of airborne emissions in release. This 80 % share of raw material and energy costs is due to a significant (70 per cent in the structure of the cost of production of its processing industry). The analysis conducted in the regions of Ukraine showed the most effective functioning of the industrial sectors of Poltava and Sumy regions. Among the regions of the Western region, the highest values of industrial indices, in particular, the share of airborne vehicles in the production, are demonstrated by Ivano-Frankivsk and Rivne, and absolute indicators are in Lviv regions. Organizational and economic mechanisms of reduction of domestic production costs are offered, which, in particular, provide for optimization of schemes of placement and interaction of industrial enterprises and improvement of management of material flows
Keywords: industry, structure, issue, gross value added, efficiency, export